Long‐term Hearing Outcomes in Patients with Enlarged Endolymphatic Duct and/or Sac on MRI. (2nd September 2014) - York, Christopher A.; Booth, Tim N.; Johnson, Romaine F.; Isaacson, Brandon; Roland, Peter S.
Abstract : Objectives: (1) Analyze the longitudinal hearing outcomes in children with evidence of dilated endolymphatic duct (ED) or endolymphatic sac (ES) on high resolution magnetic resonance imaging (HRMRI). (2) Correlate severity of hearing loss with ED/ES size and fluid‐attenuated inversion recovery (FLAIR) signal. Methods: This retrospective chart review examined medical records from 2000 to 2013 at a tertiary pediatric referral center to identify patients with evidence of enlarged ED and/or ES by HRMRI. Longitudinal audiometric data (pure tone averages [PTA]) was analyzed using chi‐squared and simple linear regression analysis. Significance was set at P =. 05. Results: Seventy‐four patients were identified with an enlarged ED or ES in at least one ear (normal ears used as controls). Audiometric data were available for 106 ears. In our patient population, increasing ED (linear regression, P <. 01, R2 = 0.35) and ES size (linear regression, P <. 01, R2 = 0.28) predicted severity of hearing loss. Increased FLAIR signal, more common in patients with abnormal ED and ES, predicted poorer hearing outcomes (linear regression, P <. 01, R2 = 0.16). Combining ED, ES, and FLAIR signal had a more pronounced effect (linear regression, P <. 01, R2 = 0.47). However, there was no evidence of progression in our data set over a mean of 32 months. Conclusions: Contrary to our current understanding, our data does not support a progressive nature for the hearing loss associated with enlargement of the ED and/or ES. It also introduces increased FLAIR signal as an additional predictor of poorer hearing outcomes.